2020
DOI: 10.1002/mrm.28244
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated MP2RAGE imaging using Cartesian phyllotaxis readout and compressed sensing reconstruction

Abstract: Purpose MP2RAGE T1‐weighted imaging has been shown to be beneficial for various applications, mainly because of its good grey‐white matter contrast, its B1‐robustness and ability to derive T1 maps. Even using parallel imaging, the method requires long acquisition times, especially at high resolution. This work aims at accelerating MP2RAGE imaging using compressed sensing. Methods A pseudo‐phyllotactic Cartesian MP2RAGE readout was implemented allowing for flexible reordering and undersampling factors. The samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
66
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(73 citation statements)
references
References 34 publications
6
66
1
Order By: Relevance
“…However, recent advances in image reconstruction based on deep learning algorithms can be used to highly accelerate the acquisition in MP2RAGE ( Lønning et al., 2019 ) and multi-shot EPI ( Bilgic et al., 2019 ). Compressed sensing ( Lustig et al., 2007 ) has also been applied to accelerate MP2RAGE acquisitions ( Trotier et al., 2019 ; Mussard et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent advances in image reconstruction based on deep learning algorithms can be used to highly accelerate the acquisition in MP2RAGE ( Lønning et al., 2019 ) and multi-shot EPI ( Bilgic et al., 2019 ). Compressed sensing ( Lustig et al., 2007 ) has also been applied to accelerate MP2RAGE acquisitions ( Trotier et al., 2019 ; Mussard et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…MP2RAGE has increased lesion and tissue contrast compared to the common MPRAGE ( Kober et al, 2012 ). Moreover, while currently the MP2RAGE sequence requires about 8 min of scanning time protocol, recent developments have shown that its acquisition time can be reduced to less than 4 min without compromising the image quality ( Mussard et al, 2020 ). Thus, it could easily be included (additionally to or instead of the MPRAGE) in a 3T MRI MS clinical protocol in order to support the CLs analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The CgH is a largely monodirectional bundle (see Mori et al, 2005; see also Wu et al, 2016) that affords itself to measurement from single-shell acquisitions that have relatively low angular resolution (e.g., 15-20 directions). It may well be possible to acquire relevant, quantitatively stable dMRI in 90s or less with available acquisitions and potentially in under a minute as dMRI acquisitions adopt newer acceleration strategies (e.g., compressed sensing acceleration; Tobisch et al, 2018; Mussard et al, 2020).…”
Section: Discussionmentioning
confidence: 99%